Práticas corporais e sexualidade: erotismo e sedução de mulheres comerciárias de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
For centuries, we have seen Brazilian women being singled out as sexual symbols, and Brazil, as the paradise of sex. This research assumes the purpose of verifying in what sense is constructed the fallacious discourse depreciating the image of the Amazonian woman and the prejudice in relation to her behavior, related to her sexuality that, until today, lasts in forged conceptions, since the time of the arrival of the first travelers. This crossed look seems to have been incorporated by the Brazilian people, who still sell the image of the Brazilian woman as a product of export. This feeling created in the period of colonization, remains alive in the XXI century, mainly, related to the Amazon woman. Centuries have passed and, yet, there is present a misconception about the woman of the North Region, related to her sexuality, sensuality and eroticism. The great question that presided over this study was to know why sexuality is the mobilizing element of the defamation of the Amazonian woman. At this angle, some questions were put to our inquiry, in order to clarify the meaning of the fallacious speech on the sexuality of the Amazonian women, considered hot still in the present times. The fieldwork assumed the point of a qualitative research and phenomenology was our methodological compass. The subjects listed were the business women of the Center of Manaus, because it is the space where the commerce is pulsating and the social relations are interspersed of power relations, including sexual harassment and the relations of sexual exchanges and patronages of the affective relationships. To guide the research, we used three categories of analysis that constructed the thesis chapters addressing issues related to body, sexuality, gender, eroticism and the game of seduction. The study shows that there is a patriarchal prejudice, since colonization, on the sexuality and eroticism of Amazonian women that was absorbed as truth in a historical cultural process. It is important to emphasize that this construction is a fallacy built to disqualify the woman from indigenous roots who, naturally, presents in her body eroticism and sensuality.
Corporal practices and sexuality: eroticism and seduction of women traders of Manaus
Keywords: Mulheres comerciárias; Business womwn; Erostismo; Sexualidade; Sexuality; Eroticism; Amazon region; CIÊNCIAS HUMANAS